Analisis Kinerja Lembaga Penegak Hukum untuk Korupsi Pada Penanganan Perkara Tindak Pidana Pencucian Uang - Nurmalasari, Dias; Mita, Aria Farah (Jurnal Ilmu Manajemen dan Bisnis, 2023)
In these times, the crime of money laundering (TPPU) has become increasingly complex and complicated by using various and varied modes. This is one of the challenges for law enforcement agencies for corruption. In accordance with the Performance Accountability Report of Law Enforcement Agencies for corruption in 2021 it is not yet optimal in handling ML cases, namely only reaching 40%. Therefore, the purpose of this research is to identify the main causes of the Law Enforcement Agency for Corruption not being optimal in handling ML cases and to analyze what factors can optimize the handling of ML cases in the Law Enforcement Agency for Corruption. The researcher uses an extensive literature review and focuses on the performance of Law Enforcement Agencies for corruption so that they can be optimal in handling ML cases. Collecting evidence using a case study research strategy with a qualitative approach through direct observation of internal sources, analysis of documents, and interviews with related parties. This study uses interactive model data analysis techniques. In handling ML cases, the Law Enforcement Agency for corruption found that there were variations of fraud used by perpetrators of criminal acts that were increasingly complex, so it was necessary to improve HR capabilities in handling ML cases. In addition, there is a need for a specific policy regarding the handling of ML cases which can then be set forth in Standard Operating Procedures.